CONDUCT OF PSYCHOLOGICAL COUNSELING AND GUIDANCE SERVICES OVER THE INTERNET: CONVERGING COMMUNICATIONS - Dincyuerek, Sibel; Uygarer, Gulen (Turkish Online Journal Educational Tech-Tojet, 2012)
Technology brings novelties among human beings' lives and human psychology is also influenced by these novelties in positive and negative way. In the study, positive contribution of the technology and the importance of counseling services were wished to be indicated. School counseling services were conducted to illustrate the importance of online counseling services in the study. The method of the study was preferred as mix-method. The population of the study is Eastern Mediterranean University of psychological counseling and guidance's undergraduate students, Turkish Cypriot School Counselors and Turkish School Counselors. Data collection instruments were determined as a scale and semi-structured interview questions. Quantitative data analysis was done according to SPSS (T-Test, One Way ANAVO, Two Ways ANAVO) and qualitative data analysis was done according to Thematic analysis. Nationality, Gender differences, school counselors views about online counseling services, school counselors students' numbers and academicians' views about online counseling services are significant variables for the study. The findings indicate that online counseling services are essential for school environment to make contribution and to provide more services to students about school counseling services.
Keywords: Program